Efficiency and Equity: Assessing the Relationship Between Health System Efficiency and Social Inclusion in Europe (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This paper investigates the relationship between health system efficiency and social inclusion in Europe. Using a two-stage empirical strategy on a panel of 25 countries over the period 2009 – 2019, we first estimate health system efficiency scores through Stochastic Frontier Analysis (SFA), where per capita health expenditure is related to a composite health index including infant mortality, life expectancy, and hospital discharges. In the second stage, these efficiency scores are introduced into pooled OLS and panel mixed-effects models to assess their association with social outcomes, measured by both the Gini index and a multidimensional index of social inclusion. The results reveal wide cross-country differences in efficiency, with Germany, Austria, and Italy among the most efficient, while Romania, Latvia, and Bulgaria rank lowest. More importantly, the analysis demonstrates that greater efficiency in health systems is systematically associated with lower inequality and higher social inclusion. These findings suggest that efficiency in health resource allocation extends beyond improved health outcomes to broader societal benefits, reinforcing the case for policies that integrate fiscal sustainability, equity, and social cohesion within the European Social Model and the UN 2030 Agenda for Sustainable Development.
Keywords: social inclusion; health system efficiency; stochastic frontier analysis; panel data; social cohesion